A natural polymer-based porous sponge with capillary-mimicking microchannels for rapid hemostasis. (15th September 2020) - Wang, Liangyu; Zhong, Yuanyuan; Qian, Chuntong; Yang, Dongzhi; Nie, Jun; Ma, Guiping
ABSTRACT: Natural polymer materials have attracted great attention in the field of hemostasis because of their wide range of source, nontoxicity, hydrophilicity, and air permeability. In the present study, two natural polymers composed of carboxymethyl chitosan (CMCS) and sodium carboxymethylcellulose (CMCNa) plus γ-(2, 3-epoxypropoxy) propytrimethoxysilane (KH560) that serves as a crosslinking agent were selected to synthesize a capillary-mimicking composite hemostatic (CCK) sponge with a low density, interconnected microchannel architecture, suitable mechanical strength, high resilience, and ultrastrong liquid absorption capacity. The introduction of a large number of hydrophilic carboxymethyl functional groups and the design of capillary-mimicking structures formed by the ice segregation-induced self-assembly (ISISA) process endowed the CCK sponges with an ultrastrong liquid absorption capacity, which significantly enhanced the hemostatic ability of the materials. Both in vivo and in vitro hemostatic experiments confirmed the potential of the CCK sponges to achieve rapid hemostasis. Additionally, cytotoxicity and hemolysis assays showed that the CCK sponges exhibited good biocompatibility and hemocompatibility. The possible hemostatic mechanism was also discussed in this study. In conclusion, the capillary-mimicking hemostatic sponge exhibits a high potential to induce rapid hemostasis in prehospital emergency and clinical settings. Statement of significance: In the present study, an oriented composite hemostatic (CCK) sponge with a capillary-mimicking structure formed by the ice segregation-induced self-assembly (ISISA) process was designed and used to achieve rapid hemostasis. The unique aligned microchannel structure of the sponge exhibited an ultrastrong capillary-mimicking action and endowed the prepared CCK hemostatic sponge with a strong liquid absorption capacity. By changing the proportion of raw materials, we could modify the unique capillary-mimicking structure with aligned microchannels. Two natural polymer-based materials with abundant hydrophilic groups were chosen to prepare the CCK sponge to fully utilize the characteristics of this structure. The oriented natural polymer-based porous sponge with capillary-mimicking microchannels exhibited a strong hemostatic ability in both in vivo and in vitro tests. The results showed that the CCK sponge with the capillary-mimicking structure has a high potential to achieve rapid hemostasis. Graphical abstract: Image, graphical abstract